Are all democracies equally good? The role of interactions between political environment and inequality for rule of law - Uwe Sunde; Matteo Cervellati; Piergiuseppe Fortunato (Institute for the Study of Labor (IZA), 2007)
Using cross-country data, we find evidence for a significant negative interaction effect between democracy and inequality in determining the quality of growth-promoting institutions like rule of law. Democracy is associated with institutions of higher quality when inequality is lower.
Keywords: 330; Demokratie; Rechtsstaat; Soziale Ungleichheit; Politische Stabilität; Institutionalismus; Welt